(untitled) (Global Journal of Science Frontier Research, 2012)
It is noticed that, in the accelerating universe, proton mass, proton size and the strong coupling constant are cosmic variable constants. Independent of the cosmic red shift and CMBR observations, cosmic acceleration can be verified by measuring the `rate of decrease’ in the proton mass. Cosmic initial conditions can be addressed with the Planck mass and the coulomb mass Based on the Mach’s principle and the characteristic Hubble mass of the present universe, it is noticed that, in the Hubble volume, critical density, observed matter density and the thermal energy density are in geometric series and the geometric ratio is 1 + ln (M 0 / M C ). In this connection, it can be suggested that -in understanding the basics of grand unification and cosmology, cosmic Hubble volume can be given a chance.